“I’m Already Seen as a Sexual Predator From Saying Hello”: Black Men’s Perception of Sexual Violence - Zounlome, Nelson O. O. (Journal of interpersonal violence, 2021)
Sexual violence is a severe and rampant issue plaguing college campuses. However, the lack of research pertaining to underrepresented students calls into question the generalizability of university education and prevention efforts. Consequently, there is a gap in the literature regarding African American men’s understanding of sexual violence. This study seeks to address this gap by examining African American university men’s conceptualization of sexual violence from their own racial and cultural perspectives. Ninety-minute semi-structured interviews were conducted with eight male African American students attending predominantly White institutions. Data were analyzed by three coders using an interpretative phenomenological approach and intersectional framework. Data were then presented to an auditor and the coders revised the themes based on the auditor’s feedback. Four themes emerged from this analysis: aggressive and violent stereotypes of Black men, othering of male survivors, racial considerations when responding to survivors, and awareness of racial injustices. These results provide evidence supporting the need for culturally grounded sexual violence education and prevention efforts to effectively reach African American men on university campuses. For example, universities may consider having African American confidential advocates and a committee of racially diverse members to run reported instances of sexual violence to reduce bias. In addition, universities may benefit from partnering with Black fraternities to empower men to be allies for social change against rape culture within their communities. For clinical work, such efforts could include incorporating explicit discussions of the impact of gendered racism on Black male survivors into session. Also, clinicians could aim to combat the internalization of the gender racist stereotypes with clients.